Case Report: Primary Ewing Sarcoma of the Penis With Multiple Metastases - Chuanxi Zheng; Yong Zhou; Yi Luo; Hongying Zhang; Chongqi Tu; Li Min (Frontiers Media S.A., 2021)
Background: Ewing sarcoma is the second most common malignant bone tumor in children, but it rarely originates from extra-skeletal sites. The commonly involved sites of soft tissue include paravertebral spaces, lower extremities, the pelvis, head, and neck, while primary extra-skeletal Ewing sarcoma (EES) located in the genitals is extremely rare.Case Presentation: We report a young patient who presented to our hospital with a painful erection of the penis and limited motion of the left hip. Magnetic resonance imaging showed a hyperintense mass with invasion of adjacent tissue in the penis and a heterogeneously high signal lesion in the left proximal femur. 18F-fluorodeoxyglucose positron-emission tomography detected widespread metastatic lesions in the bilateral lung and multiple skeletons. An incisional biopsy of the penis was performed; the histopathological findings and EWS gene translocation identified by molecular analysis confirmed the diagnosis of Ewing sarcoma. Subsequently, the punch-biopsy specimen from the left femur showed undifferentiated small round cells, a finding consistent with the microscopic presence of Ewing sarcoma metastasis. However, after the first course of multiagent chemotherapy, the penile mass did not obtain stabilization but instead grew progressively with surface ulceration and multidrug resistant bacteria infection. Despite receiving antibiotics and maximal supportive therapy, the patient died from sepsis and lung metastasis complications in the intensive care unit 2 months later.Conclusion: This case indicates that although EES as a subtype of Ewing sarcoma is rare, it can occur virtually in any soft tissue site, even in the genitals. Therefore, clinicians need to distinguish this entity from other soft tissue sarcomas with rapid progression since early diagnosis and timely treatment of EES are pivotal for a favorable prognosis.